1992
DOI: 10.1007/bf01888525
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of iohexol-240 versus iohexol-300 in abdominal CT

Abstract: Forty patients without evidence of liver, kidney, or significant cardiac disease were prospectively divided into two groups of 20, receiving either iohexol-240 or iohexol-300. A contrast load of 150 ml was administered in conjunction with a rapid scanning technique at a preselected, fixed level to include liver, renal cortex, and aorta. Peak enhancement was calculated as change in Hounsfield units (HU) over baseline for each area of interest. Mean peak enhancement and standard deviation were calculated for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Therefore, results from studies with other solid organs cannot be directly applied to the kidney. In addition, most previous reports did not perform studies in the same patient (3-7, 9), and only a few reports have described CT imaging in the same patient (10-12). Considering radiation and contrast media exposure, an intra-individual comparison study has many limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, results from studies with other solid organs cannot be directly applied to the kidney. In addition, most previous reports did not perform studies in the same patient (3-7, 9), and only a few reports have described CT imaging in the same patient (10-12). Considering radiation and contrast media exposure, an intra-individual comparison study has many limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the detectability of lesions in the liver (which is dependent on the contrast enhancement within the parenchyma) controversial results have been published with different contrast media. Some studies have shown that there is no difference between non-ionic media compared with ionic media (7,12,14,15,17,18). DEAN et al (7) showed that there were different concentrations of iodine in the tissues of the spleen and liver following metrizamide, iopamidol and iohexol injections.…”
Section: Discussionmentioning
confidence: 99%
“…Iopentol300 solution (320 mgI/ml vs 300 mgI/ml), with results comparable to the less concentrated iohexol 300 and iopentol 300. Different authors (15, 16) have suggested that the use of a reduced amount of contrast media (i.e., 32 gI vs 45 gI) or use of contrast media with a lower iodine concentration (i.e., 240 mgI/ml vs 300 mgI/ml) is preferable due to cost savings and lower iodine load, without impairing the diagnostic quality of the examination (15, 16). Figure 3 shows the liver AUC values corrected for the amount of iodine administered and the cost per gram of iodine for all four contrast agents.…”
Section: Ct Examinations Were Performed On a Philipsmentioning
confidence: 99%